Cuda z udziałem roślin i zwierząt w późnoantycznych miraculach. Próba systematyzacji - Adamiak, Stanisław (Vox Patrum, 2024)
The article tries to present and systematize the Late Antique miracles with the participation of plants and animals. The main source material is drawn from the collections of miracles such as the works of Gregory of Tours and Gregory the Great. The distinction will be made between the miracles that happened during the lifetime of a saint or after their death and between the miracles in which the plants and animals are objects or subjects of a miracle, or both at the same time.